Media and Pre-Marital Heterosexual Information Seeking Behavior among Youth in Klang Valley - Manickam, Yesuselvi; Zanuddin, Hasmah (International Journal of Psychosocial Rehabilitation, 2020)
The issue of youth sexual behaviour leading to pre-marital heterosexual sexual is a pervasive problem around the world. Active engagement and involvement on sexual activity among youth in Malaysia has brought many health and social issues; among them namely, pregnancy out of wedlock, abortion, baby dumping, transmitting STDs and HIV and AIDS (Nik Farid et al, 2018). However, the information pertaining to this issue is very limited in the mainstream media so awareness of this issue is very limited among youth and these cases are becoming increasingly common in Malaysia. By using Situational Theory of Public (STP), this study aims to gain understanding the problem recognition by youth about this issue through mass media in Klang valley. The collected data will be quantitative based on survey questionnaire that included 384 respondents from Klang Valley. Of 384 respondents, female respondents are more than male respondents in terms of participating in the survey. The findings showed that youth are aware of pre-marital heterosexual issues through the Internet, friends and newspaper with the mean score 4.33 (SD=.791), 3.88 (SD=1.045) and 3.65 (SD=1.075). In overall, the respondents had certain knowledge of the effects that youth can have it if they are involved with pre-marital heterosexual activity such as baby dumping with mean score 4.14 (SD = .831), unwanted pregnancy, 4.21 (SD=795), other health issues with mean score of 4.15 (SD=811). Social media interventional played a significant role in the constraint behaviour and youth level of involvement in their information seeking behavior related this issue.